Perceptions on the construction of knowledge in science in Elementary School using the active methodology of Blended Learning (Research, Society and Development, 2022)
Considering the low results presented by Brazilian education in global indicators such as those published by the Organization for Economic Cooperation and Development - OECD, and by other indicators such as the UNESCO Education ranking. It can be seen that Brazilian education needs improvements so that it is possible to provide students with a meaningful learning experience. Therefore, we believe that education must accompany the innovations provided mainly by digital information and communication technologies - TDICs, abandoning mechanical techniques of knowledge transmission that disregard the heterogeneity of education and increasingly inserting itself in the daily lives of students, so that they can learn in a personalized way. The present research seeks to analyze how knowledge occurs at a fundamental level in the discipline of science from the model of rotation by stations, based on the active methodology of hybrid teaching that seeks to involve TDICs in the educational process so that it is possible to customize the time and mode of learning. In the proposed model, the classes were arranged in groups (called stations), and in each station there was a specific activity to be carried out by the present group. In our conclusions, we corroborate positive results of the rotation by stations listed by the students when answering the questionnaires applied after classes.